PENGARUH MUATAN TRUK BERLEBIH TERHADAP NILAI KERUSAKAN DAN BIAYA PEMELIHARAAN JALAN RUAS CIKAMPEK-PAMANUKAN - M Abdul Aziz G; Budi Hartanto Susilo (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2018)
Cikampek-Pamanukan Road is the main route of Pantura in the area ofWest Java Province. The proportion of truck traffic in the lane tend to be higher along with the high traffic of goods. The research conducted in the Cikampek-Pamanukan section aims to analyze the magnitude of the effect of overloaded truckloads on the road damage value, to analyze the magnitude of the effect of overhead truckloads on road maintenance costs, and the costs incurred due to excessive truckloads. Methods The study was conducted by conducting a road damage survey from March to December 2016, and an overload truck survey using WIM tools from January to December 2014. The results showed the effect of overload loading on vehicle damage (ESAL) in the form of exponential curve with the equation Y = 23,722e0,0264x. The influence of overload truck volume on roaddamage resulted in Cirebon Y = 7,4823066 - 0,0000048X1 + 0, 004239X2, and Jakarta Y = 172,9392 + 0,00009X1 - 0,00830X2. The effect of overloaded truckloads on road maintenance costs with over 10% MST loading, resulting in a cost of Rp. 733.180.483,72